Concurrent cisplatin-based chemoradiation and adjuvant hysterectomy for bulky stage IB-IIA cervical cancer - Chalong Cheewakriangkrai (2018)
Objectives: To evaluate the outcomes and adverse effects of concurrent cisplatin -based chemoradiation and adjuvant hysterectomy for bulky stage IB-IIA cervical cancer. Material and Method: All eligible, thirty-four patients with bulky stage IB-IIA cervical cancer were assigned to receive weekly cisplatin 40 mg/m2 for 6 cycles concurrently with radiation followed by extrafascial hysterectomy 6 weeks after completion of radiation. Results: Estimated 5-year progression-free and disease-free survival rates of 80% were observed after a median follow-up of 42 months. The overall recurrent rate was 18%. Grade 3 neutropenia and anemia were noted in only 5.9% and 2.9%, respectively. All acute toxicities were transient and were manageable. There were no treatment-related deaths or late toxicities. Conclusion: For appropriately selected patients with bulky stage IB-IIA cervical cancer, concurrent cisplatin-based chemoradiation followed by adjuvant hysterectomy offers an effective treatment option with acceptable toxicity.